Basic College Mathematics (9th Edition)

Published by Pearson
ISBN 10: 0321825535
ISBN 13: 978-0-32182-553-7

Chapter 9 - Basic Algebra - 9.7 Solving Equations with Several Steps - 9.7 Exercises: 68

Answer

x = $\frac{-11}{3}$

Work Step by Step

Check: Replace x with -2 in the original equation 3 (2x + 5) = -7 3(2*-2 + 5) = -7 3(-4 +5) = -7 3(1) = -7 3 =-7 False The first step on the left side should have been 3 (2x + 5) is 6x + 15. 6x +15 = -7 Subtract 15 to both sides 6x +15 - 15 = -7 -15 6x = -22 Finally, divide both sides by 6 $\frac{6x}{6}$ = $\frac{-22}{6}$ x = $\frac{-11}{3}$ The solution is $\frac{-11}{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.